Reporting Sectarian Incidents: Examining the escalatory and de-escalatory discourses in the Pakistan News Media - Mohammad Zubair Iqbal; Shabir Hussain (Journal of Political Studies, 2017)
This study investigates the role of news media on reporting the sectarian conflict in Pakistan. The available scholarship suggests that media is a double-edge sword which can become an important tool to promote religious harmony and ease tension between the warring groups and at the same time it can escalate tension by exaggerating events and becoming mouthpiece of war-mongers. The researcher borrows key notions from peace journalism scholarship and applies it at a national setting. The quantitative and qualitative analyses reveal that the news media showed responsibility, exercised restraint and prioritized popular perspective while reporting on sectarian tension in the country. The study supports the key assertion in peace journalism that conflict escalation can be averted if journalists are sensitized about the consequences of irresponsible reporting especially in nascent democracies like Pakistan.